(untitled) (Journal of Electrical Engineering, 2012)
The minority carrier injection and minority carrier stored charge of an n-Si Schottky barrier diode (SBD) considering carrier recombination and blocking properties of the low-high (n-n+) are analyzed. Based on the assumption of slow variation of electric field within the quasi-neutral Si, solution of minority carrier profile is obtained. For the first time, a closed form expression for minority carrier profile p(x) for uniformly doped n-Si SBD is obtained, which is applicable for all levels of injection. Present analysis shows that minority carrier current, charge storage time and current injection ratio depend not only on the length of the n region but also on doping density, recombination within n-Si and effective surface recombination velocity at the low-high (n-n+) interface. Results obtained from the present model are also compared with experimental data available in the literature and are found to be in good agreement. Journal of Electrical Engineering The Institution of Engineers, Bangladesh Vol. EE 37, No. II, December, 2011